Impact of a physician-led exercise programme on quality of life, muscle mass and clinical response in inflammatory bowel disease patients during induction with disease-modifying therapy: a study protocol. Issue 1 (6th September 2022) - Mc Gettigan, Neasa; Hanley, Marion; Skelly, Fiona; Dowling, Jennifer; Dunne, Ruth; Morrin, Martina M; McCaffrey, Noel; O'Toole, Aoibhlinn; Boland, Karen
Abstract : Introduction: Biologic and small-molecule therapies have revolutionised the treatment of moderate-to-severe inflammatory bowel disease (IBD). A significant proportion of patients experience early or delayed treatment failure. Patients with IBD with greater visceral obesity are less likely to respond to biologics. Sarcopenia has been identified as a predictor of disease severity and need for rescue therapy in acute severe ulcerative colitis. The aim of this study is to assess the feasibility of a physician-derived exercise programme in patients with IBD commencing biologic or small-molecule therapy in addition to the effect on physical fitness, body composition and objective measures of quality of life, fatigue scores and disease activity. Methods and analysis: This is a randomised controlled feasibility study comparing the effects of a physician-derived exercise programme and standard medical care (biologic/small-molecule therapy) with standard care alone in patients with moderate to severe IBD. Patients with IBD in the intervention group will undergo a structured exercise programme for 20 weeks. Both IBD groups will carry out body composition, disease activity and quality-of-life assessments at baseline, week 12 and week 26. The primary objective is to assess the feasibility of the physician-derived exercise programme in patients with IBD commencing disease-modifying therapies. Secondary endpoints include a change in cardiorespiratory fitness, disease activity/inflammation, fatigue, health-related quality of life outcomes and body composition between the two IBD groups. Exploratory endpoints include validation of anterior thigh ultrasound for sarcopenia screening, assessment of proinflammatory cytokines and markers of immunometabolism. Ethics and dissemination: This study has received ethical approval from the Beaumont Hospital Ethics committee on 22 October 2021 (reference number 21/21). Data generated or analysed during this study will be published as an article and supplementary appendix in relevant medical journals. The data will also be presented at national and international conferences. Trial registration number: NCT05174754 .